(untitled) (Revista de Investigaciones Universidad del Quindío, 2011)
The present study evaluated the different biological properties of the total ethanolic extract and the alkaloid fraction obtained from leaves of Sansevieria trifasciata, such as the antimicrobial activity against Staphylococcus aureus, Escherichia coli and Candida albicans, and cytotoxic activity on Vero cells; and antitumor activity in murine myeloma and HepG2. Likewise, phytochemical screening was conducted to determine some secondary metabolites present in the leaves and the toxicity was measured with Artemia salina. It was possible to determine the presence of alkaloids, leucoanthocyanidins, steroidal saponins, coumarins, sesquiterpene lactones, glycosides cardiac, carotenoids and carbohydrates. There was no presence of flavonoids, naphtha and/or anthroquinones and tannins. No antibacterial activity was found against E. coli, but the ethanol extract showed activity against S. aureus and C. Albicans. None of the extracts showed cytotoxic activity against Vero cells or antitumor mouse myeloma cells. The alkaloid fraction contained antitumor activity in HepG2 cells. The mean lethal concentration in Artemia salina extracts was 146.41 mg / mL.